Effects of Synergistic Fermentation of Yeast in Yunnan Rice Wine and Rhizopus oryzae on Physicochemical Properties and Flavor Substances of Rice Wine - Yang HE; Yiting FENG; Haowen WU; Yizhen QIN; Yanling LU; Ziqi GAO; Fangyu FAN (Shipin gongye ke-ji)
To improve traditional sweet rice wine stability and flavor, yeasts with high alcohol and ester production were isolated, purified, and screened from Yunnan traditional sweet rice wine, and the strain was identified by morphological observation and molecular biology methods, with its alcohol and ester production characteristics analyzed. Effects of different yeasts synergized with Rhizopus oryzae on the quality of sweet rice wine was assessed by physicochemical indexes, sensory evaluation, and amino acid and volatile compositions. Results showed that a high alcohol production yeast strain LF05 and a high ester production yeast strain PL10 were isolated and screened, which were identified as Saccharomyces cerevisiae and Rhodotorula mucilaginosa. Compared with the control, S. cerevisiae LF05 synergised with Rhizopus oryzae fermented sweet rice wine increased the alcoholic strength (6.80vol%) and volatile alcohols (44.27 mg/L) by 23.64% and 36.60%. It reduced the bitter amino acids (329.25 μg/mL) by 41.19%. Compared with the control group Rhodotorula mucilaginosa PL10 synergized synergised with Rhizopus oryzae fermented sweet rice wine volatile esters (7.29 mg/L), sweet amino acids (425.18 μg/mL), and fresh amino acids (740.51 μg/mL) were increased by 220.39%, 154.64%, and 134.82%, as well as the sensory score (86 points) increased by 64.48%. In conclusion, the synergistic fermentation of S. cerevisiae LF05 and R. mucilaginosa PL10 with Rhizopus oryzae can improve the problem of taste and blandness of commercial sweet rice wine, which provides a reference and theoretical basis for the preparation of sweet rice wine in Yunnan Province.